Determination of Escitalopram in Biological Samples by Dispersive Liquid-Liquid Microextraction Combined with GC-MS/MS - GUAN Qing-lin, XIE Wen-kai, Lü Chen-xi, et al (Fayixue Zazhi, 2020)
Objective To establish a method for determination of escitalopram in biological samples by ultrasound-assisted ionic liquid-dispersive liquid-liquid microextraction combined with gas chromatography-tandem mass spectrometry （GC-MS/MS） and provide evidences for forensic determination of cases related to escitalopram. Methods The 1-hexyl-3-methylimidazolium hexafluorophosphate （[C6MIM][PF6]） was selected as an extract solvent to process biological samples. Ultrasound-assisted extraction was used on the samples. Then the samples were detected by GC-MS/MS. Results The linear range of escitalopram in blood and liver were 5.56-1 111.10 ng/mL and 0.025-5.00 mg/g, respectively. The correlation coefficient （r） were greater than 0.999, limit of detection （LOD） were 4.00 ng/mL and 2.00 μg/g, limit of quantitation （LOQ） were 14.00 ng/mL and 6.00 μg/g, respectively. The extraction recovery rates were all greater than 50%, the interday and intraday precision were less than 20%. Escitalopram was detected in blood and liver samples from the actual poisoning case by this method with a content of 1.26 μg/mL and 0.44 mg/g, respectively. Conclusion The ultrasound-assisted ionic liquid-dispersive liquid-liquid microextraction combined with GC-MS/MS is environment friendly, rapid, has good enriching effect and consumes less organic solvent and can be used for forensic determination of escitalopram related cases.